Customer Satisfaction with E-banking Services: A Case Study of Undergraduate Students - Manandhar, Raju Bhai; Chalise, Mahananda; Chapagain, Sadikshya (PYC Nepal Journal of Management, 2024)
The growth of e-banking has been accelerated by digital platforms that enable customers to access financial services remotely. Increased smartphone usage and internet accessibility have driven higher adoption, particularly among students and general consumers. Customer satisfaction, influenced by factors such as security, reliability, and convenience, is crucial to the success of online banking services. This study aims to assess the impact of security, reliability, and convenience on customer satisfaction with e-banking services. A causal-comparative research design was employed, targeting undergraduate students from Pokhara University who use e-banking services. A total of 209 students were selected through convenience sampling. Primary data was collected via a structured questionnaire based on a five-point Likert scale. Correlation and regression analyses were used to interpret the data and derive conclusions. The study identifies a significant relationship between security, reliability, convenience, and customer satisfaction with e-banking services. Notably, security and convenience are key determinants of customer satisfaction, whereas reliability has a comparatively minor influence. These findings suggest that banks and financial institutions (BFIs) should prioritize enhancing the security, reliability, and ease of use of their digital platforms. Additionally, government support in developing secure network infrastructure is essential for optimizing customer satisfaction with online banking. Future research could explore other influencing factors using larger sample sizes and alternative methodologies.